Analisis Pengendalian Persediaan Bahan Baku Jenis Gelas 240 mL dengan Metode EOQ (Economic Order Quantity) di PT. Trijaya Tirta Dharma - SUSANTI SUNDARI; SAPUTRO WIJAYA NEGARA (Industrika : Jurnal Ilmiah Teknik Industri, 2017)
PT. Trijaya Tirta Dharma is an industrial company who produces products in form of the bottled drinking water. In produces several types of drinking water such as glass 150 mL and 240 mL, bottles of 600 mL and 1500 mL and the final product is gallon 19 L. Analysis of cup material inventory control by using method EOQ in PT. Trijaya Tirta Dharma is to reduce production cost, especially in the cost of materials infentory type 240 mL glass tipe. Raw material inventory control have a functions to avoid shortage or excess. The less quantity of inventory make it loss of the opprtunity to get the benefit when demand more than the supply make of material inventory is buildup the materials of 240 mL glass in the material warehouse. The material inventory control basically is to achieve the afficiency level of the cost in the inventory. The other way to control the supplay of materials is make the purchase according to the production plan with the accurate calculations in order not to deficient and excess of inventory materials. PT. Trijaya Tirta Dharma can save on fees amounted to Rp. 59.730.000 in 2011 with total inventory Rp. 4.956.487.000 whereas in 2012 can save the ordering fee Rp. 52.710.000 with a total inventory Rp. 3.718.612.000, in 2013 the company could save the ordering fee Rp. 152.315.000 with a total inventory Rp. 5.107.466.000 whereas in 2014, PT. Trijaya Tirta Dharma can save the ordering fee Rp. 152.100.000 with a total inventory Rp. 8.169.420.000. the survey results is known that the purchase of materials by using EOQ method is more effective and efficient than without EOQ. So, the purchase by using this method make frequency of purchase materials is more less. Keywords: 240 mL Glass Raw Material, Control Analysis, Inventory of Raw Materials